2020
DOI: 10.11591/ijere.v9i3.20635
|View full text |Cite
|
Sign up to set email alerts
|

Affective engagement in academic reading: What EFL student teachers reveal

Abstract: Academic reading is an inescapable task in higher education. Due to its importance for study success, students are required to maintain their academic reading engagement. With engagement, they would be enabled to persevere and be more spirited in their reading efforts. However, not all students perceive academic reading positively, particularly in EFL learning environment where English reading is seen as something daunting. Academic reading engagement is essentially determined by a number of dimensions, one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Recent perspectives on second language teaching devote attention to the active engagement of learners in reading by personally engaging with it, connecting to their life experience, personal world, and background knowledge to make personal meaning, not just to receive the intended message (Burns & Siegel, 2018;Grabe & Stoller, 2019;Lee, 2014;Pietarinen et al, 2014;Unrau & Quirk, 2014;Wang & Eccles, 2011, Watkins, 2017. Text comprehension depends on the interaction of textual, contextual, and reader-related variables (Roe et al, 2005), which necessarily, but not exclusively, involve emotion and motivation (Yulia et al, 2020). It follows then that learners' reading comprehension depends on their ability to coordinate background knowledge, linguistic skills, strategies, cognition and affection, and the degree to which they are engaged cognitively and emotionally with the text.…”
Section: Second Language Reading Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent perspectives on second language teaching devote attention to the active engagement of learners in reading by personally engaging with it, connecting to their life experience, personal world, and background knowledge to make personal meaning, not just to receive the intended message (Burns & Siegel, 2018;Grabe & Stoller, 2019;Lee, 2014;Pietarinen et al, 2014;Unrau & Quirk, 2014;Wang & Eccles, 2011, Watkins, 2017. Text comprehension depends on the interaction of textual, contextual, and reader-related variables (Roe et al, 2005), which necessarily, but not exclusively, involve emotion and motivation (Yulia et al, 2020). It follows then that learners' reading comprehension depends on their ability to coordinate background knowledge, linguistic skills, strategies, cognition and affection, and the degree to which they are engaged cognitively and emotionally with the text.…”
Section: Second Language Reading Instructionmentioning
confidence: 99%
“…Besides, Philp and Duchesne (2016) noted that past research referred to task engagement as cognitive involvement, and argued that behavioral, social and affective dimensions should be included. In particular, affective engagement which involves eliciting emotional reactions to a text (Unrau, & Quirk, 2014) has recently been recognized as a crucial element in second language acquisition (Philp & Duchesne, 2016), and proved to enhance EFL reading instruction (Yulia et al, 2020). Despite its value for reading comprehension instruction (Duke et al, 2021), affective engagement with texts appears to be sparingly practiced in the EFL classroom, especially in the educational setting of Vietnam.…”
mentioning
confidence: 99%
“…Reading attitude is a system of feelings that can lead readers to avoid or approach reading activities [21]. Furthermore, feeling toward reading will drive learners to approach or avoid reading [22], [23] This means that attitude towards reading will affect students' actions in reading, and engagement in reading will influence reading ability [16]. However, a study by Lukhele [24], which used Pearson's Product-Moment Correlation, reported that no correlation was found between reading ability and reading attitudes, r(84)=0.08, p=0.46.…”
Section: Introductionmentioning
confidence: 99%
“…Academic reading is a necessary scholarly activity for learners to engage with at university (X. Liu & Read, 2020;Yapp & Graaff, 2021), an essential skill (Yulia et al, 2020) for success in education. Although it is an important skill for students, many researchers have identified several reasons students fail to complete required readings.…”
Section: Introductionmentioning
confidence: 99%